2020
DOI: 10.3390/microorganisms8111750
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacillus cereus Phage vB_BceP-DLc1 Reveals the Largest Member of the Φ29-Like Phages

Abstract: Bacillus phage φ29 and its relatives have been considered as one of the most important model organisms for DNA replication, transcription, morphogenesis, DNA packaging studies, and nanotechnology applications. Here, we isolated and characterized a new member of the φ29-like phage, named Bacillus cereus phage vB_BceP-DLc1. This phage, with a unique inserted gene cluster, has the largest genome among known φ29-like phages. DLc1 can use the surface carbohydrate structures of the host cell as receptors and only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The supernatant was collected into a new centrifuge tube, mixed with an equal volume of isopropanol, and then maintained at −20°C for 30 min. After centrifugation at 12,000 × g and 4°C for 30 min, pellets were washed with 75% ethanol three times, then dissolved in 50 μl of deionized water, and stored at −20°C before use ( Chun et al, 2020 ; Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was collected into a new centrifuge tube, mixed with an equal volume of isopropanol, and then maintained at −20°C for 30 min. After centrifugation at 12,000 × g and 4°C for 30 min, pellets were washed with 75% ethanol three times, then dissolved in 50 μl of deionized water, and stored at −20°C before use ( Chun et al, 2020 ; Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was collected into a new centrifuge tube, mixed with an equal volume of isopropanol, and then maintained at −20 • C for 30 min. After centrifugation at 12,000 × g and 4 • C for 30 min, pellets were washed with 75% ethanol three times, then dissolved in 50 µl of deionized water, and stored at −20 • C before use (Chun et al, 2020;Yang et al, 2020). The DNA library was constructed using the QIAseq TM FX DNA Library Kit (Qiagen, Hilden, Germany), and highthroughput sequencing was carried out using an Illumina HiSeq TM 2500 (Illumina, San Diego, CA, United States) according to the manufacturer's instructions.…”
Section: Stability Studiesmentioning
confidence: 99%
“…However, due to advances in viral classification techniques and the addition of other phi29-like phages in Genbank, this work is outdated. Recently, Li, et al [ 23 ] isolated one of the newest members of this group, DLc1, and concluded that the now present 30 phi29-like phages should be included within the Salasvirus genus. However, this study failed to use multiple reticulate phylogeny methods for this classification and relied only on basic genome comparison methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is comparable to SARS-CoV-2 in terms of size, being one of the smallest bacteriophages of Bacillus subtilis (Anderson et al, 1966 ). In addition, phage ɸ29 is very accessible and has been extensively studied as a model for viral replication (Li et al, 2020 ). We think bacteriophage ɸ29 may be a good virus model for studying disinfection procedures.…”
Section: Discussionmentioning
confidence: 99%